Improvements in High-Density Lipoprotein Quantity and Quality Contribute to the Cardiovascular Benefits by Anti-tumor Necrosis Factor Therapies in Rheumatoid Arthritis: A Systemic Review and Meta-Analysis - Luo, Yonghong; Ren, Xiaolei; Weng, Shuwei; Yan, Chunhui; Mao, Qiaoxia; Peng, Daoquan (Frontiers in Cardiovascular Medicine, 2021)
Objectives. Inflammation plays important roles in atherosclerotic cardiovascular diseases, but the interaction between inflammation and lipid profile is largely unrevealed in humans. Patients with rheumatoid arthritis (RA) suffer from a higher risk of cardiovascular diseases (CVDs). Decreased total cholesterol (TC) and high-density lipoprotein (HDL) were prevalent in patients with RA. Anti-tumor necrosis factor (TNF) therapies relieve disease activity and decrease CVDs risk in RA, but their comprehensive effects on lipid profile are unclear. This study aims to investigate the changes in blood lipid profile along time in RA patients accepting anti-TNF therapies by meta-analysis. Methods. MEDLINE, Embase, and CENTRAL were searched for eligible literature. Data of lipids were classified into short-, mid-, and long-term according to treatment duration. Meta-analyses were performed to compare lipid levels before and after treatments. Results. A total of 44 records and 3935 patients were included in the meta-analyses. Anti-TNF therapies were associated with significant increases in TC (MD: +0.14, +0.23, +0.26 mmol/l, respectively) and HDL (MD: +0.11, +0.12, +0.11 mmol/l, respectively) in the short-, mid-, and long-term; anti-TNF therapies were associated with increased low-density lipoprotein (LDL) (MD: +0.06 mmol/l) and Apolipoprotein A1 (Apo A1) (MD: +0.07 g/l) in the short-term but not in the mid-term and long-term; Triglyceride (TG) and Apolipoprotein B (Apo B) do not change significantly in all periods; pro-atherosclerotic indexes (TC/HDL, Apo B/ApoA1, and LDL/HDL) tend to decrease in the short- and mid-term, but return to baseline in the long-term after TNF inhibition. Conclusion. Anti-TNF therapies were related to a long-term raised HDL level, which, together with evidence of improved HDL function, may contribute partially to the decreased CVDs risk by TNF inhibition.